Accelerated discovery of stable lead-free hybrid organic-inorganic perovskites via machine learning - Shuaihua Lu (Nature Portfolio, 2018)
Conventional trial-error method is inefficient in discovering new functional materials in vast chemical and structural space. Here Lu et al. use machine learning techniques to screen out the most promising lead-free organic-inorganic perovskites with proper bandgap and stability from thousands of them in a flash.